Capacity Building in Basic Education schools in Egypt in the Light of Strategic Planning - Attia Ghazala (International Journal of Instructional Technology and Educational Studies)
This study aimed to develop a Model of Capacity Building for improving the Quality of Basic Education Schools in Dakahlia Governorate, Egypt. The research method used the descriptive research as it suits the case and to accomplish the aims of the study the researcher relied on a survey to gather information about the real status of the school capacity building in Basic Education in Egypt. The main stages were: a preliminary study, development of the design and the product model, validation testing through pre-experiment, and product disseminationThe commitment of the Egyptian Government to improve the quality of education in Basic Education Schools over the last decade has continued to pose a serious challenge to all stakeholders in the education system. One of the strategic approaches to improving education quality is through the employment of capacity-building activities. This paper deals with the role of strategic planning in capacity building for Basic Education Schools in Dakahlia. Specifically, attention will be on the strategic planning activities for principals in Basic Education Schools to build their school capacity. Efforts will focus on how the strategic planning activities have affected the performance of the schools in Dakahlia and how this has also been reflected in the level of improvement of developing schools in Egypt. Finally, what can be learned from capacity building in Basic Education Schools in Egypt will be highlighted.